Review of Research on Overcapacity Measurement and Evaluation - Hu, Hanyu (Transactions on Economics, Business and Management Research, 2024)
Overcapacity will have an important impact on economic and social development, so it is a key research topic in academia. To study the problem of overcapacity, it is necessary to accurately measure overcapacity. Since different scholars have different interpretations of the connotation and denotation of overcapacity, a variety of overcapacity evaluation methods have emerged. This paper will review the domestic and foreign literature on the measurement and evaluation of overcapacity, analyze and compare different methods, and lay a theoretical foundation for subsequent relevant research, in order to provide help for China’s overcapacity reduction work.